The Effect of Sex Education Counseling on Knowledge in Preventing Sexual Violence in Pre Adolescent Children at MI Baitul Mukmin - Melati Puspita Sari (Fetus : Journal of Midwifery, 2023)
Indonesia is currently experiencing a sexual violence emergency with the targets of the abusers being mostly minors. One of the factors causing these cases is the lack of knowledge of children related to sex education. The purpose of the study was to determine the effect of sex education counseling on knowledge in preventing sexual violence. This research is a quantitative study with a pre-experimental design with a one group pretest-posttest design. The research sample was 47 respondents with total sampling technique. Data analysis techniques using the Wilcoxon test. The results showed that children's knowledge before counseling was obtained majority in the less category as many as 25 children (53.2%). While after counseling, the results of the good category were 40 children (85.1%). Based on the results of the Wilcoxon test, p value = 0.000 (p value <0.05) means that there is a significant influence between pretest and posttest after counseling on sex education. It is hoped that schools can collaborate with health workers in efforts to prevent early sexual violence in children by using leaflet media tools and animated videos, because this can clarify the delivery of material and respondents easily accept the information conveyed.